PENGEMBANGAN PEMBELAJARAN WIRAUSAHA DI ERA COVID-19 BERBASIS SOCIETY 5.0 DI DESA BONGOIME KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Titin Dunggio; Ayu Humagi; Sri Ayinda Umar (Journal of Hulonthalo Service Society (JHSS), 2023)
The Covid-19 pandemic has had a significant impact on various sectors of life, including entrepreneurship. Many business owners have been forced to close their businesses due to social restrictions and a decrease in people's purchasing power. On the other hand, the community needs empowerment efforts to develop entrepreneurial potential amid the difficult conditions during the Covid-19 pandemic. The concept of Society 5.0 which emphasizes technology and innovation can be a solution to develop adaptive entrepreneurial learning in the Covid-19 era. The purpose of this activity is to develop entrepreneurial learning in Bongoime Village by utilizing the concept of Society 5.0, especially in the context of post-Covid-19 pandemic recovery. Through surveys and interviews, high entrepreneurial potential was identified among the community, despite facing technological knowledge constraints. The training program involved 30 participants and covered business planning, digital marketing, and product innovation. Evaluation results showed a significant increase in participants' understanding of technology-based entrepreneurship. In addition, the formation of five new entrepreneurial groups signifies the success of this program in encouraging collaboration and creativity among participants.